t=18⋅(a-y+z)

Rewrite the equation as 18⋅(a-y+z)=t.

18⋅(a-y+z)=t

Multiply both sides of the equation by 8.

8⋅18⋅(a-y+z)=8⋅t

Cancel the common factor of 8.

Cancel the common factor.

8⋅18⋅(a-y+z)=8⋅t

Rewrite the expression.

1⋅(a-y+z)=8⋅t

1⋅(a-y+z)=8⋅t

Multiply a-y+z by 1.

a-y+z=8⋅t

a-y+z=8t

Subtract a from both sides of the equation.

-y+z=8t-a

Subtract z from both sides of the equation.

-y=8t-a-z

-y=8t-a-z

Multiply each term in -y=8t-a-z by -1.

(-y)⋅-1=8t⋅-1+(-a)⋅-1+(-z)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=8t⋅-1+(-a)⋅-1+(-z)⋅-1

Multiply y by 1.

y=8t⋅-1+(-a)⋅-1+(-z)⋅-1

y=8t⋅-1+(-a)⋅-1+(-z)⋅-1

Simplify each term.

Multiply -1 by 8.

y=-8t+(-a)⋅-1+(-z)⋅-1

Multiply (-a)⋅-1.

Multiply -1 by -1.

y=-8t+1a+(-z)⋅-1

Multiply a by 1.

y=-8t+a+(-z)⋅-1

y=-8t+a+(-z)⋅-1

Multiply (-z)⋅-1.

Multiply -1 by -1.

y=-8t+a+1z

Multiply z by 1.

y=-8t+a+z

y=-8t+a+z

y=-8t+a+z

y=-8t+a+z

Solve for y t=1/8*(a-y+z)